The Effect of a Character Education-Based Explicit Instruction Model on Biology Learning Outcomes in the Digestive System Topic among Grade XI Senior High School Students - Sarah Ummi Athiya; Khairuna Khairuna (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study examined the effect of a character education-based Explicit Instruction learning model on students’ biology learning outcomes in the digestive system topic. The study was motivated by the tendency of biology instruction to be teacher-centered, resulting in low student participation, limited conceptual understanding, and insufficient integration of character values. The objective was to determine the influence of the Explicit Instruction model integrated with character education on students’ learning outcomes and character development. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group pretest-posttest design. The sample consisted of an experimental class and a control class. Data were collected through pretests, posttests, and character education questionnaires. Data analysis included normality, homogeneity, and independent sample t-tests. The findings revealed that the experimental class showed a greater improvement in learning outcomes, with the mean score increasing from 48.5 to 80, while the control class improved from 43 to 79.5. Furthermore, the character education questionnaire yielded an average score of 88.93%, categorized as very good. These results indicate that the character education-based Explicit Instruction model positively affects both students’ biology learning outcomes and character development.